2011
DOI: 10.1002/cae.20319
|View full text |Cite
|
Sign up to set email alerts
|

A novel educational platform to teach CANopen field bus

Abstract: This article presents a practical communications course focused on the CANopen field bus. The learning platform is composed by four nodes with real industrial devices, common in automation applications. The course has been put into practice by the CITCEA-UPC in collaboration with Schneider Electric Spain. The course is devised both for university students and industry professionals. The problem proposed to the students is the configuration of a CANopen bus and the automation of a machine movement sequence. ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The design of multi degree of freedom manipulator is very typical, and other more complex and powerful operation processing system is also based on this aera [8] . After testing, it is found that the multi degree of freedom manipulator based on the 485 bus has stable performance and strong anti-interference ability, and the cost of development and production is relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…The design of multi degree of freedom manipulator is very typical, and other more complex and powerful operation processing system is also based on this aera [8] . After testing, it is found that the multi degree of freedom manipulator based on the 485 bus has stable performance and strong anti-interference ability, and the cost of development and production is relatively low.…”
Section: Discussionmentioning
confidence: 99%